PARENTS’ATTITUDES, THEIR ACCEPTANCE OF THE COVID-19 VACCINES FOR CHILDREN AND THE CONTRIBUTING FACTORS IN NAJRAN, SAUDI ARABIA - Khaled Ali Alrashah; Tariq Nasser Haqawi; Mohsen Abdullah Alrashah; Ahmed Saleh Alkhiwani; Ibahim Ahmed Alrashah; Naif Salem Aljamaher; Naif Abdullah Alrashah; Layla Hussain Mohammed Awaji (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: The COVID-19 pandemic is still ongoing, so it is critical to immunize the majority of people, including children, to achieve herd immunity against the pandemic. As parents are the ones who ultimately decide whether or not to vaccinate their children, this study was conducted to determine parental acceptance and hesitancy toward vaccinating their children against COVID-19, as well as their knowledge of and concerns regarding vaccination against COVID-19, as well as factors that might influence their willingness to vaccinate in Najran city, Saudi Arabia. Methods: In February 2022, a cross-sectional, questionnaire-based study using a convenient and snowball sampling technique was carried out. Parents of children between the ages of 5 and 11 were given access to an online self-administered survey. The poll was, however, open to parents of children under the age of 5. Using the Raosoft sample size calculator, the minimum necessary sample size was determined to be 384 under the assumptions of a 5% margin of error and a 95% confidence level. A p value of less than 0.05 was deemed significant for the statistical analysis, which was carried out using SPSS version 27. To examine the relationship between demographic factors and how drivers affect parents’ willingness to vaccinate their children against COVID-19, a chi-square test was performed. Through multivariate regression analysis, the predictors of vaccine hesitancy were identified. Results: A total of 464 responses were collected and subjected to data analysis. More than half of the parents were male (56.9%) and between the ages of 26 and 40 (56.7%). Most parents have children aged between 5–11 years (73.5%). Of parents, 72.2% showed vaccine hesitancy and were 9.5 times less likely to immunize their children against COVID-19. About 27.8% of the parents were ready to vaccinate their children against COVID-19 as soon as possible, compared to 15.51% of parents who were not at all interested in vaccinating their children. Parents under 25 (34.48%) and over 41 (37.79%), non-Saudi (40.59%), holding postgraduate and higher degrees (39.5%), earning more than 10,000 SAR per month (34.96%), working as healthcare professionals (40.36%) and in government sectors (33.93%), self-employed (33.33%), with three to five children (35.26%) and male (31.33%) demonstrated significantly high willingness to vaccinate their children against the COVID-19 vaccine compared to their counterparts. Parents who concur that COVID-19 vaccination may have serious adverse effects in children, who believe that COVID-19 is an uncommon disease and does not require vaccination, have had a family member infected withCOVID-19 with severe symptoms, who were unvaccinated and had severe to moderate symptoms after vaccination, showed significantly higher unwillingness to vaccinate their children against COVID-19. Parents who take safety precautions and do not believe that new vaccines provide an increased risk had higher vaccination intentions for their children. A positive impact of mandatory childhood vaccination was noted on the COVID-19 vaccination. Parents with children suffering from any chronic disease exhibited a 9.9 times higher hesitancy to vaccinate their children against COVID-19. A total of 47.8% of parents had come across or heard about anti-COVID-19 vaccination campaigns. A lack of adequate safety data, potential future consequences, and vaccine efficacy were the main concerns with COVID-19 vaccines. The primary information source for COVID-19-related information was the Saudi Ministry of Health (MOH). Conclusions: Parents’ hesitation to get the COVID-19 vaccine at a significant rate may compromise the success of the ongoing vaccination campaign. The development and implementation of multi-component interventions are required. Hospital- and community-based programs must be used to get in touch with parents.